Influence of Maternal Glycemic Status (HbA1c) at Delivery and Risk of Hypoglycemia in Infants of Diabetic Mothers (BIRDEM Medical Journal, 2012)
Objective: To examine the influence of maternal HbA1c level at delivery and risk of hypoglycemia in infants of diabetic mothers. Method: This case-control study was done with sixty neonates born to diabetic mothers in BIRDEM hospital. Out of sixty neonates, 30 neonates who developed hypoglycemia during the first 24 hours of age were considered as cases and another 30 neonates who did not develop hypoglycemia during the first 24 hours were considered as controls. Maternal glycemic status was examined by measurement of Glycosylated hemoglobin (HbA1c) and level of